Republic of Kosovo : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
This article summarizes the financial performance and crisis management of the Republic of Kosovo. Kosovo's economic condition shows stability in systematic risks, but it also has vulnerabilities. Kosovo banks are exposed to macrofinancial risks because of its open economy, but the Central Bank of the Republic of Kosovo (CBK) has immensely promoted the growth and stability of the banking sector. CBK should also monitor certain interest rates, tax rates, and foreign rates. The current system should allow the growth of microfinance institutions to reach the competition in the global banking sector.